TO THE ISSUE OF REGULATORY AND LEGAL CONSOLIDATION OF ADMINISTRATIVE AND LEGAL INSTRUMENTS OF PREVENTIVE ACTIVITIES OF THE NATIONAL POLICE OF UKRAINE (Bulletin of criminological association of Ukraine, 2023)
The article is devoted to the study of the regulatory and legal consolidation of the administrative and legal instruments of preventive activities of the National Police of Ukraine. It was emphasized that the application of administrative and legal tools for the preventive activities of the National Police, firstly, should be in clear compliance with the generally recognized international and European standards of police activity, and secondly, the basic basis for the implementation of the arsenal of relevant administrative and legal tools, with the help of which the implementation is achieved tasks defined for the National Police of Ukraine regarding the implementation of preventive activities should be an integral mutually agreed normative legal framework, which defines the types and regulates their implementation.It is substantiated that the normative-legal acts that establish the administrative-legal instruments of preventive activities of the National Police constitute a system complex of interconnected elements combined into a certain structural unity, which can be organized according to various characteristics and parameters that determine the types and regulate the procedures , the grounds and features of the application of administrative and legal instruments, which are used to achieve the tasks set before the National Police of Ukraine regarding the implementation of preventive activities aimed at preventing violations of the population’s daily life and ensuring the optimal functioning of a safe environment.It was concluded that the «integration» of prevention as a legal phenomenon in all the tasks assigned to the National Police of Ukraine testifies to the wide range and complex structure of the system of normative and legal acts that establish and define the administrative and legal instruments of the National Police’s preventive activities, which, in turn, , requires a systematic approach using the classification distribution of the relevant regulatory and legal acts.On the basis of the generalization of theoretical and legal approaches to the classification of regulatory and legal acts, the author’s vision was formed regarding the criteria for the systematization of regulatory and legal acts, which determine the administrative and legal instruments of preventive activities of the National Police.
Keywords: National Police of Ukraine; police activity; preventive activity; prevention; normative legal act; classification; iteria for the classification of normative legal acts; administrative and legal instruments; instruments of public administration